Embodied Pedagogical Governance: Cultivating Spiritual Habitus Through Tarbiyatul Aulad in an Islamic Boarding School - Eko Kurniawanto; Noorthaibah Noorthaibah; Bahrani Bahrani; Taufikin Taufikin; Mohd Syakir Mohd Rosdi (Universitas Nurul Jadid, 2026)
Amid globalization and rapid social change, Islamic education faces growing pressure to sustain religious values that are lived in everyday practice rather than merely taught, yet how such values are internalized through organized institutional life remains insufficiently understood. This study examines how the principles of Tarbiyatul Aulad fi al-Islam, a classical Islamic framework for the upbringing and character formation of children, are enacted in the daily life of an Islamic boarding school, and how routines, role modeling, and the educational environment interact to shape the spiritual habitus of the santri. Adopting a qualitative intrinsic case study design, the research drew on in-depth interviews, participatory observation, and document analysis involving twenty informants comprising students, ustadz, kiai, and parents. The data were analyzed thematically and validated through source, methodological, and theoretical triangulation. The findings show that value internalization occurs not through any single activity but through the mutually reinforcing convergence of structured routines, the observable conduct of educators, and a deliberately maintained social environment, while disconfirming cases reveal that the santri retain interpretive agency within this structure. The study contributes the notion of habitus by design and frames embodied pedagogical governance as a lens that reconceives character formation as a problem of educational management. These insights imply that pesantren can strengthen value internalization by deliberately aligning daily schedules, exemplary conduct, and environmental arrangements as a single, coordinated strategy of institutional management.